The impact of the 2021 Thrifty Food Plan benefit re-evaluation on SNAP participants’ short-term food security and health outcomes - Leung, Cindy W.; Wolfson, Julia A. (Frontiers in Public Health, 2023)
Introduction The Supplemental Nutrition Assistance Program (SNAP) is the largest federal nutrition assistance program in the United States, and played a critical role in mitigating food insecurity during the COVID-19 pandemic. In 2021, the updated Thrifty Food Plan (TFP), which provides the basis of SNAP benefit allotments, led to a 21% monthly benefit increase for SNAP participants. The objective of this study was to examine the effects of the TFP re-evaluation on food insecurity, diet quality, and mental health using a natural experiment design. Methods A longitudinal, web-based study was conducted among 1,004 United States adults with incomes at or below $65,000 in September 2021 (prior to the policy change) and February 2022 (after the policy change). Outcomes of interest included household food security, diet quality, perceived stress, and anxiety/depression, assessed using validated instruments. We used difference-in-differences regression modeling to assess the effects of the policy change on participants’ outcomes, adjusting for sociodemographic covariates. Qualitative responses to open-ended questions about the policy change were analyzed using thematic analysis. Results Prior to the policy change, SNAP participants had significantly worse food insecurity, lower diet quality scores, and higher perceived stress and anxiety/depression when compared to non-participants (all Ps < 0.05). After adjustment for differences in sociodemographic characteristics, there were no significant effects of the TFP re-evaluation on food insecurity, diet quality, and mental health outcomes among SNAP participants relative to non-participants (all Ps > 0.05). Qualitative responses suggested that rising food prices and growing inflation potentially negated the benefits of the policy change; however, most SNAP participants described the added benefits as helpful in purchasing additional food supplies and offsetting other household costs during this period. Discussion The TFP benefit increase may have helped to prevent inflation-related disparities in food insecurity and health outcomes from widening among SNAP participants and non-participants. Further research is needed to determine the long-term impacts of this policy change.